Long-term patient satisfaction and durability of laparoscopic anti-reflux surgery in a large Danish cohort: study protocol for a retrospective cohort study with development of a novel scoring system for patient selection - Katrine Hass Rubin; Jonas Sanberg Ljungdalh; Jesper Durup; Kim Christian Houlind (BMJ Open)
Introduction Laparoscopic anti-reflux surgery is standard of care in surgical treatment of gastro-oesophageal reflux disease and is not without risks of adverse effects, including disruption of the fundoplication and postfundoplication dysphagia, in some cases leading to reoperation. Non-surgical factors such as pre-existing anxiety or depression influence postoperative satisfaction and symptom relief. Previous studies have focused on a short-term follow-up or only certain aspects of disease, such as reoperation or postoperative quality of life. The aim of this study is to evaluate long-term patient-satisfaction and durability of laparoscopic anti-reflux surgery in a large Danish cohort using a comprehensive multimodal follow-up, and to develop a clinically applicable scoring system usable in selecting patients for anti-reflux surgery.Methods and analysis The study is a retrospective cohort study utilising data from patient records and follow-up with patient-reported quality of life as well as registry-based data. The study population consists of all adult patients having undergone laparoscopic anti-reflux surgery at The Department of Surgery, Kolding Hospital, a part of Lillebaelt Hospital Denmark in an 11-year period. From electronic records; patient characteristics, preoperative endoscopic findings, reflux disease characteristics and details on type of surgery, will be identified. Disease-specific quality of life and dysphagia will be collected from a patient-reported follow-up. From Danish national registries, data on comorbidity, reoperative surgery, use of pharmacological anti-reflux treatment, mortality and socioeconomic factors will be included. Primary outcome of this study is treatment success at follow-up.Ethics and dissemination Study approval has been obtained from The Danish Patient Safety Agency, The Danish Health Data Authority and Statistics Denmark, complying to Danish and EU legislation. Inclusion in the study will require informed consent from participating subjects. The results of the study will be published in peer-reviewed medical journals regardless of whether these are positive, negative or inconclusive.Trial registration number Clinicaltrials.gov (NCT03959020).